Highly Axial Magnetic Anisotropy in a N3O5 Dysprosium(III) Coordination Environment Generated by a Merocyanine Ligand. Issue 43 (21st September 2016) - Selvanathan, Pramila; Huang, Gang; Guizouarn, Thierry; Roisnel, Thierry; Fernandez‐Garcia, Guglielmo; Totti, Federico; Le Guennic, Boris; Calvez, Guillaume; Bernot, Kévin; Norel, Lucie; Rigaut, Stéphane
Abstract: A spiropyran‐based switchable ligand isomerizes upon reaction with lanthanide(III) precursors to generate complexes with an unusual N3 O5 coordination sphere. The air‐stable dysprosium(III) complex shows a hysteresis loop at 2 K and a very strong axial magnetic anisotropy generated by the merocyanine phenolate donor. Abstract : Spiropyran‐based switchable ligand : The 4f ion‐induced isomerization of a spiropyran ligand produces a mononuclear merocyanine dysprosium complex with single‐molecule magnet behavior. The air‐stable dysprosium(III) complex shows a hysteresis loop at 2 K and a very strong axial magnetic anisotropy generated by the merocyanine phenolate donor.